Pengaturan Tentang Pengungsi Dan Tanggung Jawab UNCHR Bagi HAM Para Pengungsi - Melatunan, Hendrik O; Tahamata, Lucia Charlota Octovina; Leatemia, Wilshen (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The changes and developments of the times until now have not provided a reference for the development of international law as a whole, including in dealing with refugees.Purposes of the Research: This study aims to examine and analyze UNHCR's responsibility for the human rights of refugees in terms of international law and the regulation of refugees in terms of international law.Methods of the Research: This type of research is normative juridical where the research is carried out by collecting primary, secondary and tertiary data obtained using library research. The data that has been collected is analyzed qualitatively, the description of which is arranged systematically based on legal disciplines to achieve clarity on the issues to be discussed.Results of the Research: The results of the study show that the international standard rules that have been agreed upon by the nations of the world related to the legal arrangements for refugees are contained in the 1951 Convention and the 1967 Protocol on the Status of Refugees. Another instrument is the Declaration of Human Rights because the refugee issue is closely related to human rights issues. In addition, there is also the UNHCR Statute which contains the roles, duties and authorities of UNHCR as an international institution dealing with refugees. UNHCR is an international institution formed, sheltered and an extension of the United Nations to specifically deal with issues related to refugees. On December 14, 1950, the UNHCR Statute established the function of UNHCR, namely to provide international protection, under the auspices of the United Nations, to refugees. In particular, UNHCR has four roles, namely as initiator, facilitator, mediator & conciliator, and as determination. In dealing with Myanmar refugees in Thailand, UNHCR uses 3 methods to deal with the refugee problem, namely Repatriation, Local Integration, and Resslement.